Increasing Yield of 2,3,5,6-Tetramethylpyrazine in Baijiu Through Saccharomyces cerevisiae Metabolic Engineering - Cui, Dan-Yao; Wei, Ya-Nan; Lin, Liang-Cai; Chen, Shi-Jia; Feng, Peng-Peng; Xiao, Dong-Guang; Lin, Xue; Zhang, Cui-Ying (Frontiers in Microbiology, 2020)
Baijiu is a traditional distilled beverage in China with a rich variety of aroma substances. TTMP is an important component in Baijiu and has the function of promoting cardiovascular and cerebrovascular health. During the brewing of Baijiu, the microorganisms in jiuqu produce acetoin and then synthesize TTMP, but the yield of TTMP is very low. In this work, 2,3-butanediol dehydrogenase (BDH) coding gene BDH1 and another BDH2 gene were deleted or overexpressed to evaluate the effect on the content of acetoin and TTMP in Saccharomyces cerevisiae. The results showed that the acetoin synthesis of strain α5-D1B2 was significantly enhanced by disrupting BDH1 and overexpressing BDH2, leading to a 2.6-fold increase of TTMP production up to 10.55 mg/L. To further improve the production level of TTMP, the α-acetolactate synthase (ALS) of the pyruvate decomposition pathway was overexpressed to enhance the synthesis of diacetyl. However, replacing the promoter of the ILV2 gene with a strong promoter (PGK1p) to increase the expression level of the ILV2 gene did not result in further increased diacetyl, acetoin and TTMP production. Based on these evidences, we constructed the diploid strains AY-SB1 (△BDH1::loxP/△BDH1::loxP) and AY-SD1B2 (△BDH1::loxP-PGK1p-BDH2-PGK1t /△BDH1::loxP-PGK1p-BDH2-PGK1t) to ensure the fermentation performance of the strain is more stable in Baijiu brewing. The concentration of TTMP in AY-SB1 and AY-SD1B2 was 7.58 and 9.47 mg/L, respectively, which represented a 2.3- and 2.87-fold increase compared to the parental strain. This work provides an example for increasing TTMP production in S. cerevisiae by genetic engineering, and highlight a novel method to improve the quality and beneficial health attributes of Baijiu.